Bibliometric Analysis of the Worldwide Research Productivity on Oral Health Related Quality of Life (Ohrql) - Hernandez-Vasquez, A. (2017)
ABSTRACT Objectives Worldwide scientific production on Oral Health Related Quality of Life (OHRQL) has not been explored. The objective of this study was to perform a bibliometric analysis of global research productivity on OHRQL. Methods An electronic search for original articles was conducted using the Web of Science database, with the terms: “Oral Health Related Quality of Life” AND “OHRQL”. Bibliometric indicators were investigated by analyzing annual research output, languages, countries, journals, authors, institutions, and citations. Results Bibliographic research retrieved 1099 papers for the period 1996-2016. The yearly quantitative distributions of articles were highly correlated (R2=0.90). The mostly used languages were English (1084 articles), Portuguese (6 articles) and German (5 articles). Retrieved articles were published by 73 different countries. The largest contributors are the USA (182), Brazil (168), and England (158). In Latin America (without Brazil), Peru (9), Chile (8), Mexico (5), and Colombia (2), were other countries with a scientific production. The articles were published in 188 journals. The top three journals which published the most articles were Community Dentistry and Oral Epidemiology (102), Health and Quality of Life Outcomes (48), and Journal of Oral Rehabilitation (47), responsible for 18% of the publication. The total number of authors for all articles was 2876. John MT. published the most documents in this field (49 articles), followed by Locker D. (43 articles), and McGrath C. (39 articles). The three most prolific institutions were University College London (62) University of Hong Kong (59) and University of Toronto (49). The citation count was 16430. Average citations per item were 14.95, and the h-index was 54. Conclusions These results shown an idiomatic, regional and intraregional gap on OHRQL research production, and articles has been published in journals with high international reputation in Oral Health and QoL. Brazil has special contributions to the body of OHRQL.